Infection prevention and control practices in the Pediatrics and Child Health Department of Tikur Anbessa Specialized Hospital, Ethiopia - Yilma, Mengistu; Taye, Girma; Tefera, Muluwork; Tassew, Berhan; Fentie, Atalay Mulu; Abebe, Workeabeba (Frontiers in Public Health, 2024)
Background Infection prevention and control (IPC) is a set of practices that are designed to minimize the risk of healthcare-associated infections (HAIs) spreading among patients, healthcare workers, and visitors. Implementation of IPC is essential for reducing infection incidences, preventing antibiotic use, and minimizing antimicrobial resistance (AMR). The aim of the study was to assess IPC practices and associated factors in Pediatrics and Child Health at Tikur Anbessa Specialized Hospital. Methods In this study, we used a cross-sectional study design with a simple random sampling method. We determined the sample size using a single population proportion formula with the assumption of a 55% good IPC practice, a 5% accepted margin of error, and a 15% non-response rate and adjusted with the correction formula. The final sample size was 284 healthcare workers. The binary logistic regression model was used for analysis. The World Health Organization (WHO) Infection Prevention and Control Assessment Framework (IPCAF) tool was used to assess IPC core components. Result A total of 272 healthcare workers participated in the study, with a response rate of 96%. Of the total participants, 65.8% were female and 75.7% were nurses. The overall composite score showed that the prevalence of good IPC practices among healthcare workers was 50.4% (95% CI: 44.3–56.5). The final model revealed that nursing professionals and healthcare workers who received IPC training had AORs of 2.84 (95% CI: 1.34–6.05) and 2.48 (95% CI: 1.36–4.52), respectively. The final average total IPCAF score for the IPC level was 247.5 out of 800 points. Conclusion The prevalence of good IPC practice was suboptimal. The study participants, who were nursing professionals and healthcare workers who received IPC training, showed a statistically significant association with the IPC practice level. The facility-level IPCAF result showed a “Basic” level of practice based on the WHO categorization. These evidences can inform healthcare workers and decision-makers to identify areas for improvement in IPC practice at all levels. Training of healthcare workers and effective implementation of the eight IPC core components should be strengthened to improve suboptimal practices.